Correlation of Water Quality with OCR and SOD of Humpback Grouper in Net Cages in Concrete Ponds with Different Stocking Densities - Nugroho, Sefilia Adhi; Gunanti Mahasri; Abdul Manan (Grouper, 2025)
The humpback grouper (Cromileptes altivelis) is one of the high-value commodities in Indonesia. Humpback grouper production from the cultivation sector has not been able to reach the expected production volume. The Floating Net Cage method is the latest technology in humpback grouper cultivation, but obstacles from weather and environmental factors are very large. The author is interested in conducting research on the stress levels of humpback grouper cultivated in the innovation of net cage cultivation media placed in concrete ponds with different stocking densities. The results showed that water quality parameters were no longer the main factor causing stress in fish raised in net cage cultivation media in concrete ponds. This was shown from the results of the SPSS model output with multiple linear correlation analysis with a significance value of OCR at 0.538 and SOD at 0.112. Stocking density treatment was more influential as a cause of stress in grouper fish at a significance value <0,05.